The Effect of the Work-Based Learning Training Model on the Creativity of Training Participants at Job Training Center Bojonegoro - Ristanto, Ristanto (Yayasan Sukma, 2022)
The importance of human resources is based on the fact that human resources are the essential elements of every company. Human resources can determine the advantages of a company because human resources are goal makers, innovators, communication, creativity, and strategy for the company. This study aimed to determine the effect of the Work Based Learning training model on trainees’ creativity at the Job training centre (Balai Latihan Kerja, BLK) Bojonegoro. This research is qualitative, categorized explicitly as a qualitative program evaluation. The sample in this study amounted to 100 trainees at BLK Bojonegoro. The results showed a high scale of creativity (85.5%), the tasks of the training participants (83.4%), support for learning (78.8%), and clear goals (76%). In training models where exposure to real-world constraints, opportunities, policies, and regulations is mandatory, work-based learning occupies an essential niche in participants’ experiences.